Perceptions of Teachers and Learners of the Effects of COVID-19 on the Teaching and Learning process in Selected Secondary Schools in Kapiri- Mposhi District, Zambia - Kabeta, Rachel; Chilinga, Givers; Sakakombe, Leonard (African Journal of Education and Practice, 2022)
Purpose: The purpose of this study was to examine the perceptions of teachers and learners of the effects of Covid-19 on the teaching and learning process in the selected secondary schools in Kapiri- Mposhi District. Methodology: Ten schools were selected using random sampling from the urban and rural parts of the district, from which a total of 197 participants comprising 100 grade 9 and 12 learners and 97 teachers, were sampled. A questionnaire, face to face interviews and focus group discussions were also used to collect data for this study. Findings: The findings of the study revealed that COVID-19 was viewed to have had affected the teaching and learning negatively, as it was considered to have led to negative effects such as the closure of schools, loss of learning time, ineffective teaching and learning, poor or unequal access to learning opportunities, especially between learners in the urban and rural located schools regarding online learning. Out of 197 respondents, most of the participants (90.9%) agreed that COVID-19 may lead to unequal access to educational resources, and also that school closures may negatively impact teaching and learning outcomes, especially for the underprivileged. Further, 88.8%, 87.3%, 86.8% and 85.8% of the respondents were of the opinion that learners may substantially lag behind especially in reading and mathematical subjects, stigmatization of infected learners and staff may heighten absenteeism, school closures may put strain on parents and teachers to provide childcare and manage distance (remote) learning while learners were out of school, and risky behavior may increase that may lead to increased teenage pregnancies and substance abuse among learners, respectively. Unique Contribution to Theory, Practice and Policy: The study contributes to literature by providing more insight on how the Covid-19 pandemic affected the teaching and learning in the selected schools, it provides knowledge and insights which could also be used to understand the effect of the pandemic on education in general and thus help in finding solutions for such emergencies in future.